2016
DOI: 10.1016/j.trpro.2016.05.454
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aftertreatment Device and Driving Conditions on Black Carbon, Ultrafine Particle and NOx Emissions for Euro 5 Diesel and Gasoline Vehicles

Abstract: Ultrafine particle, black carbon and NOx emissions from Diesel and gasoline passenger cars have been investigated in this work, as well as influences of aftertreatment device and driving conditions (the cold start, urban, rural and motorway conditions…) on emissions. Experiments have been carried out on chassis dynamometer bench with Artemis urban, road and motorway driving cycles and NEDC (New European Driving Cycle). Exhaust from Euro 5 Diesel vehicles equipped with additive and catalysed particle filter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
2
11
0
1
Order By: Relevance
“…That being said, the total proportion of idle time is not the only factor: the timing and number of engine restarts and the warm-up penalty caused by engine shutdown at idle also influence the relative PM and PN results; this applies whether the Stop&Start system is active or inactive. The magnitude of the emissions from vehicle 1 are reasonably similar to those reported elsewhere [7,15]. Importantly, when Stop&Start was turned on, the vehicle met the Euro 6 PN limit over the WLTC, despite (presumably) not being calibrated to that cycle.…”
Section: Vehiclesupporting
confidence: 83%
See 1 more Smart Citation
“…That being said, the total proportion of idle time is not the only factor: the timing and number of engine restarts and the warm-up penalty caused by engine shutdown at idle also influence the relative PM and PN results; this applies whether the Stop&Start system is active or inactive. The magnitude of the emissions from vehicle 1 are reasonably similar to those reported elsewhere [7,15]. Importantly, when Stop&Start was turned on, the vehicle met the Euro 6 PN limit over the WLTC, despite (presumably) not being calibrated to that cycle.…”
Section: Vehiclesupporting
confidence: 83%
“…Anderson et al [3] subjected two Euro 6 diesel vehicles to a range of chassis dyno tests, reporting that PM emissions were always under 1 mg/km; PN emissions varied between test cycles and inertia settings with higher PN emissions over the NEDC than the WLTC. Cédric et al [7] tested several Euro 5 Diesel-DPF and DISI vehicles over multiple driving cycles and reported that cold start was responsible for both a high proportion of PN results and a high proportion of the uncertainty associated with those results. Wei et al [27] also report finding cold start and high load during the first 200 seconds to be a massive contributor to particulate emissions (measured as PM in their study).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7: As Figure 6. Figure A1: Total PN [93,95,104,105,108,109,150,158,[161][162][163]170,195,204,212,226,248,[271][272][273][274]…”
Section: Appendix Bmentioning
confidence: 99%
“…Various aftertreatment devices (such as the diesel oxidation catalyst (DOC), the diesel particulate filter (DPF), the selective catalytic reduction (SCR), or NO X trap and the three-way catalyst (TWC)) are being used to bring the pollutant emissions below regulatory levels. Although these technologies make it possible to significantly reduce regulated compound emissions, they affect some emissions of pollutants. Catalyzed or additive DPF reduce particle mass emission, with efficiency near 100%, but they might induce an increase of fine and ultrafine particle emissions and affect NO 2 , volatile organic compounds, PAH, BTEX, and black carbon (BC) emissions. The actual impacts of these after-treatment technologies on unregulated pollutant emissions are not fully known. , The recent study by Louis et al showed that catalyzed DPF vehicles emitted about 3 to 10 times more carbonyl compounds and particles than additive DPF vehicles, respectively, during urban driving cycles, while additive DPF vehicles emitted 2 and 5 times more BTEX and carbonyl compounds during motorway driving cycles.…”
Section: Introductionmentioning
confidence: 99%